INTENSITY OF THE DYNAMICS OF PHYSICAL PREPAREDNESS IN THE PROCESS OF STUDENTS GROWING UP WITH DIFFERENT LEVELS OF INTELLIGENCE - E. M. Revenko; T. F. Selova (Russian State Vocational Pedagogical University, 2016)
The purpose of the investigation is the scientific substantiation forthe implementation of a differentiated approach to the organization of physical education on the basis of accounting students individually-typological features of the age.Methods. Motor abilities of students are studied by measuring: force (backbone dynamometry), strength endurance (pulling up on the bar), speed-strength abilities (long jump from their seats), as well as high-speed capacity (running at 30, 60 or 100 meters, depending on the age), aerobic endurance (running at 1000 or 3000 m, depending on age). The dynamics of the integrated physical preparedness (DIPP) of each student is estimated by calculating the arithmetic mean value of the growth rate of the development of motor abilities listed above (the results of 5 tests). Evaluation of general intelligence (GI) of schoolchildren in 8, 10 and 11 classes, students of 1 - 3 courses carried out by the test of R. Amthauer adapted by L. A. Yasyukova [13], and the 6 classes pupils - through the intellectual test (GIT) [1].Results. It was experimentally established that students of 6, 8, 10, 11 grades and 1 - 3 courses at higher intelligence level have a low dynamics of physical fitness. On the contrary, students with a lower level of intelligence revealed a high dynamics of physical fitness. Marked discrepancies in the dynamics of the development of mental and motor areas of maturing personality are interpreted as individual-typological features of age-related development. Based on these facts it is concluded that the organization of physical education on the basis of program-regulatory approach with common unified requirements involved, will not allow to create conditions for highquality physical education of the younger generation and the formation of a sustainable motivation for self-employment by physical exercises.Scientific novelty. Scientific evidence of sustained differences in the dynamics of the physical fitness of students with different levels of general intelligence on the basis of experimental research is presented for the first time.Practical significance. The findings serve as the basis for the developing a differentiated approach to the organization of physical education based on individually-typological features of the age. Different development trajectories, due to different rates closer to the level of «maturity» functions require presentation to the students differentiated by the complexity requirements of motor tasks, and as a result, the relevant criteria for evaluation of their physical readiness.